Asuhan Keperawatan pada Pasien Gangguan Integritas Kulit dan Jaringan dengan Penerapan Perawatan Luka Ganggren Menggunakan Hydrogel - Laurina Tuto Beleker; Veroneka Yosefpa Windahadayani; Sri Indaryati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Gangrenous wounds can be caused by increased blood sugar or hyperglycemia. Gangrenous wounds persist for a long time, and if not treated properly, can progress to sepsis. This requires longer and more expensive treatment, and can have fatal consequences, requiring amputation of the gangrenous wound. Therefore, one Evidence-Based Practice (EBP)-based intervention is treating gangrenous wounds using hydrogel. This case study aims to provide nursing care to patients with impaired skin and tissue integrity with the application of gangrenous wound treatment using hydrogel. This case study method uses a descriptive method with a nursing care approach. Nursing care was provided to three respondents who met the criteria: patients with gangrenous wounds due to diabetes mellitus and hospitalization. Data were collected through interviews, observations using the Bates-Jansen Wound Assessment tool (BWAT) scale, and physical examinations. The results of the EBP wound care application using hydrogel showed changes in each patient. Patient 1, based on the BWAT scale, scored 96 cm (grade 4) on the first day, 96 (grade 4) on the second day, 75 (grade 4) on the third day, 12 cm (grade 1) on the second day, 12 cm (grade 1) on the third day, 9 cm (grade 1) on the third day, and 63 cm (grade 4) on the first day, 63 (grade 4) on the second day, and 48 (grade 4) on the third day. It was concluded that changes were observed in all patients, with the wound size decreasing and the wound condition improving. It is recommended that nurses apply hydrogel for the treatment of gangrenous wounds.